2015
DOI: 10.1515/hmbci-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix in obesity – cancer interactions

Abstract: Obesity or overweight is a risk factor for several health disorders such as type 2 diabetes, hypertension, and certain cancers. Furthermore, obesity affects almost all body systems including the extracellular matrix (ECM) by generating a pro-inflammatory environment, which are associated with abnormal secretions of several cytokines or hormonal substances, for example, insulin-like growth factors (IGFs), leptin, and sex hormones. These chemical mediators most likely have a great impact on the ECM. Accumulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 147 publications
(132 reference statements)
0
11
0
Order By: Relevance
“…Mammary adipocytes have been particularly well studied, as obesity is a known risk factor for breast cancer (13, 14) and significant cross-talk occurs between the epithelial and adipose tissue compartments in the gland (15, 16). Studies have demonstrated that adipocytes drive morphogenesis ex vivo and are essential for development of the mammary epithelium in vivo (15, 16).…”
Section: Introductionmentioning
confidence: 99%
“…Mammary adipocytes have been particularly well studied, as obesity is a known risk factor for breast cancer (13, 14) and significant cross-talk occurs between the epithelial and adipose tissue compartments in the gland (15, 16). Studies have demonstrated that adipocytes drive morphogenesis ex vivo and are essential for development of the mammary epithelium in vivo (15, 16).…”
Section: Introductionmentioning
confidence: 99%
“…The current study also examined the expression levels of hyaluronidase-1 (Hyal-1), a major tumor-derived hyaluronidase ( 15 ). Dysregulation of different ECM components may favor the neoplastic process ( 16 ). Various cells, belonging to the ECM, are also important in tumor initiation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Pathological events involved in obesity aethiology, such as inflammation and ECM modulation, also represents key steps in cancer development and progression (Barreto et al, ), so the hypothesis of a crucial implication of MMPs in obesity‐related carcinogenesis has been largely underlined. In the past, MMPs were thought to have a role exclusively in invasion and metastasis processes, but recent studies demonstrated that they are also deeply involved in several steps of cancer formation and during the growth of tumor cells by releasing of cell membrane bound precursors of some growth factors, or the inhibition of apoptosis pathways.…”
Section: Estrogen Receptors: “Genomic” and “Non‐genomic” Actions In Rmentioning
confidence: 99%